SHR4z, a novel decoy effector from the haustorium of the parasitic weed Striga gesnerioides, suppresses host plant immunity. Issue 3 (31st December 2019) - Su, Chun; Liu, Hai; Wafula, Eric K.; Honaas, Loren; de Pamphilis, Claude W.; Timko, Michael P.
Summary: Cowpea ( Vigna unguiculata ) cultivar B301 is resistant to races SG4 and SG3 of the root parasitic weed Striga gesnerioides, developing a hypersensitive response (HR) at the site of parasite attachment. By contrast, race SG4z overcomes B301 resistance and successfully parasitises the plant. Comparative transcriptomics and in silico analysis identified a small secreted effector protein dubbed Suppressor of Host Resistance 4z (SHR4z) in the SG4z haustorium that upon transfer to the host roots causes a loss of host immunity (i.e. decreased HR and increased parasite growth). SHR4z has significant homology to the short leucine‐rich repeat (LRR) domain of SOMATIC EMBRYOGENESIS RECEPTOR‐LIKE KINASE (SERK) family proteins and functions by binding to VuPOB1, a host BTB‐BACK domain‐containing ubiquitin E3 ligase homologue, leading to its rapid turnover. VuPOB1 is shown to be a positive regulator of HR since silencing of VuPOB1 expression in transgenic B301 roots lowers the frequency of HR and increases the levels of successful SG4 parasitism and overexpression decreases parasitism by SG4z. These findings provide new insights into how parasitic weeds overcome host defences and could potentially contribute to the development of novel strategies for controlling Striga and other parasitic weeds thereby enhancing crop productivity and food security globally. Abstract : See also the Commentary on this article by Delavault, 226 : 641–643 .